blaNDM-5-positive and mcr-9-carrying Escherichia coli lineages in wild Andean condors feeding at landfills in South America - Danny Fuentes-Castillo; Víctor Escobar-Gimpel; Bruna Fuga; Herrison Fontana; Fábio P. Sellera; Valentina Aravena-Ramírez; Fernanda Esposito; Daniela Castro-Tardón; Elder Sano; Montserrat del Campo-Parod; Jorge Barraza-Schulmeyer; Paula Aravena; et al. (Veterinary Microbiology, 2026)

Gut colonization of semi-aquatic turtles inhabiting the Brazilian Amazon by international clones of CTX-M-8-producing Escherichia coli - Meire Maria da Silva; Fábio Parra Sellera; João Pedro Rueda Furlan; Valentina Aravena-Ramírez; Danny Fuentes-Castillo; Bruna Fuga; Alexandre José dos Santos Fróes; Alana Lislea de Sousa; Felício Garino Junior; Nilton Lincopan (Veterinary Microbiology, 2025)

Bee pollination affects coffee quality, yield, and trade-offs within them - Natalia Aristizábal; Silvia E. Mora-Mena; Alejandra Martínez-Salinas; Adina Chain-Guadarrama; Danny Castillo; Juan B. Murillo; Jimmy Porras; Taylor H. Ricketts (Agriculture, Ecosystems & Environment, 2025)

Gut colonization by extended-spectrum β-lactamase-producing Escherichia coli in dairy herd in Brazil: successful dissemination of a One Health clone - Luciana Sartori; Fábio P. Sellera; Taiana T. Silva-Pereira; Bruna Fuga; Danny Fuentes-Castillo; Milena Dropa; Quézia Moura; Miriam R. Fernandes; Larissa Rodrigues; Fernanda Esposito; Elder Sano; Mario A. R. Aleman; et al. (Veterinary Research Communications, 2024)

Antibiotic resistance in wildlife from Antarctic Peninsula - Josefina Gutiérrez; Daniel González-Acuña; Danny Fuentes-Castillo; Karina Fierro; Carlos Hernández; Loreto Zapata; Claudio Verdugo (Science of The Total Environment, 2024)

Contribution of agricultural ashes and HDPE as a waste material for a sustainable environment applied to the stabilization of a low plasticity clay soil - Juan Martín García Chumacero; José Luis Gonzales Macedo; Danny Jhardenson Sánchez Castillo (Innovative Infrastructure Solutions, 2024)

Stenotrophomonas maltophilia Belonging to Novel Sequence Types ST473 and ST474 in Wild Birds Inhabiting the Brazilian Amazonia - Gislaine Dalazen; Fábio Parra Sellera; Danny Fuentes-Castillo; Elder Sano; Herrison Fontana; Brenda Cardoso; Fernanda Esposito; Luis Fábio Silveira; Eliana Reiko Matushima; Nilton Lincopan (Current Microbiology, 2024)

Human health risk assessment due to mercury use in gold mining areas in the Ecuadorian Andean region - Carlos Mestanza-Ramón; Samantha Jiménez-Oyola; Alex Vinicio Gavilanes Montoya; Danny Daniel Castillo Vizuete; Giovanni D'Orio; Juan Cedeño-Laje; Doménica Urdánigo; Salvatore Straface (Chemosphere, 2023)

Assessment of Hg pollution in stream waters and human health risk in areas impacted by mining activities in the Ecuadorian Amazon - Carlos Mestanza-Ramón; Samantha Jiménez-Oyola; Alex Vinicio Gavilanes Montoya; Danny Daniel Castillo Vizuete; Giovanni D’Orio; Juan Cedeño-Laje; Salvatore Straface (Environmental Geochemistry and Health, 2023)
Illegal gold mining activities have contributed to the release and mobilization of Hg and environmental degradation in many parts of the world. This study aims to determine the concentration of Hg in five provinces of the Amazon Region of Ecuador, in addition to assessing the risk to human health of exposed populations, applying deterministic and probabilistic methods. For this purpose, 147 water samples were collected in rivers and streams crossing and/or located near mining areas. As a result, 100% of the samples analyzed exceeded the maximum permissible limit (MPL) according to the water quality criteria for the preservation of aquatic life of the Ecuadorian regulations, while 7% of the samples exceeded the MPL for drinking water. On the other hand, considering the European Environmental Quality Standard (EQS) for surface water bodies, in our study, 100% of the samples exceed the maximum permissible limit (0.07 µg/L), and with respect to the Canadian water quality guidelines, 35% of the samples exceed the permissible limit (0.001 mg/l) for drinking water, and 100% of the samples exceed the limit for life in water bodies (0.0001 mg/l). The risk assessment revealed that the probability of developing adverse health effects from exposure to Hg is below the recommended limits according to the probabilistic assessment; this is in relation to the criterion of residential and recreational use of water resources. However, it was identified that the child population doubles the acceptable systemic risk level according to the results of the deterministic assessment in the residential scenario. This information can be used by decision-makers to implement strategies to reduce Hg contamination and exposure of the population in Ecuadorian Amazonian rivers.

Evaluation of the Importance of rural tourist attractions in Riobamba Canton, Ecuador - Danny Daniel Castillo Vizuete; Alex Vinicio Gavilanes Montoya; Gabriela Estefanía Román Santamaría (Environment Systems and Decisions, 2023)

Genomic evidences of gulls as reservoirs of critical priority CTX-M-producing Escherichia coli in Corcovado Gulf, Patagonia - Danny Fuentes-Castillo; Daniela Castro-Tardón; Fernanda Esposito; Ingrith Neves; Larissa Rodrigues; Herrison Fontana; Bruna Fuga; José L. Catão-Dias; Nilton Lincopan (Science of The Total Environment, 2023)

Genomic data reveal international lineages of critical priority Escherichia coli harbouring wide resistome in Andean condors ( Vultur gryphus Linnaeus, 1758) - Danny Fuentes‐Castillo; Fernanda Esposito; Brenda Cardoso; Gislaine Dalazen; Quézia Moura; Bruna Fuga; Herrison Fontana; Louise Cerdeira; Milena Dropa; Jürgen Rottmann; Daniel González‐Acuña; José L. Catão‐Dias; et al. (Molecular Ecology, 2020)
Critical priority pathogens have globally disseminated beyond clinical settings, thereby threatening wildlife. Andean Condors ( Vultur gryphus ) are essential for ecosystem health and functioning, but their populations are globally near threatened and declining due to anthropogenic activities. During a microbiological and genomic surveillance study of critical priority antibiotic‐resistant pathogens, we identified pandemic lineages of multidrug‐resistant extended‐spectrum β‐lactamase (ESBL)‐producing Escherichia coli colonizing Andean Condors admitted at two wildlife rehabilitation centres in South America. Genomic analysis revealed the presence of genes encoding resistance to hospital and healthcare agents among international E. coli clones belonging to sequence types (STs) ST162, ST602, ST1196 and ST1485. In this regard, the resistome included genes conferring resistance to clinically important cephalosporins (i.e., CTX‐M‐14, CTX‐M‐55 and CTX‐M‐65 ESBL genes), heavy metals (arsenic, mercury, lead, cadmium, copper, silver), pesticides (glyphosate) and domestic/hospital disinfectants, suggesting a link with anthropogenic environmental pollution. On the other hand, the presence of virulence factors, including the astA gene associated with outbreak of childhood diarrhoea and extra‐intestinal disease in animals, was identified, whereas virulent behaviour was confirmed using the Galleria mellonella infection model. E. coli ST162, ST602, ST1196 and ST1485 have been previously identified in humans and food‐producing animals worldwide, indicating that a wide resistome could contribute to rapid adaptation and dissemination of these clones at the human–animal–environment interface. Therefore, these results highlight that Andean Condors have been colonized by critical priority pathogens, becoming potential environmental reservoirs and/or vectors for dissemination of virulent and antimicrobial‐resistant bacteria and/or their genes, in associated ecosystems and wildlife.

A relapsing fever Borrelia and spotted fever Rickettsia in ticks from an Andean valley, central Chile - Sebastián Muñoz-Leal; Arlei Marcili; Danny Fuentes-Castillo; Mauricio Ayala; Marcelo B. Labruna (Experimental and Applied Acarology, 2019)